2018
DOI: 10.1136/emermed-2018-208032
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged length of stay in the emergency department and increased risk of hospital mortality in patients with sepsis requiring ICU admission

Abstract: Background and objectivesDelayed patient admission to the intensive care unit (ICU) from the ED is common in China. Patients with severe sepsis or septic shock requiring ICU admission are in need of specialised monitoring and tailored treatment. Delayed admission to the ICU might be associated with adverse clinical outcomes for patients with sepsis.MethodsPatients with sepsis admitted to the ICU from the ED from January 2010 to April 2018 were retrospectively identified from a clinical data warehouse. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 25 publications
1
81
1
1
Order By: Relevance
“…A previous study showed that clinical outcomes were not significantly different between early and delayed ICU admissions in sepsis patients. [13] In contrast, Zhang et al showed increased in-hospital mortality when sepsis Emergency Medicine International patients requiring ICU admission stayed longer than 12 hours in the ED [14]. Several reasons may cause delayed ICU admissions including delayed decision by the ED physician, shortage of ICU beds, waiting for radiologic examination, and ED crowding.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that clinical outcomes were not significantly different between early and delayed ICU admissions in sepsis patients. [13] In contrast, Zhang et al showed increased in-hospital mortality when sepsis Emergency Medicine International patients requiring ICU admission stayed longer than 12 hours in the ED [14]. Several reasons may cause delayed ICU admissions including delayed decision by the ED physician, shortage of ICU beds, waiting for radiologic examination, and ED crowding.…”
Section: Discussionmentioning
confidence: 99%
“…Even if there is no causal relationship between longer ED stay and mortality, longer ED stay has shown harmful consequences [ 21 ]. There were numerous studies reported about relationships between prolonged LOS and increased mortality in various situations [ 22 , 23 ]. Guttmann et al analyzed a nationwide data of Canadian ED data and found that longer waiting patients in ED showed higher short-term mortality [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guttmann et al analyzed a nationwide data of Canadian ED data and found that longer waiting patients in ED showed higher short-term mortality [ 22 ]. A more recent retrospective study also announced that ED LOS was an independent risk factor for in-hospital mortality among sepsis patients requiring ICU admission [ 23 ]. In addition, our finding suggested that higher mortality might be mainly due to a higher incidence of cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a prolonged LOS at an ED is independently associated with an increased risk of in-hospital mortality in critically ill patients, even in those without time-sensitive diseases requiring ICU admission such as severe sepsis or septic shock. [14,15] Increased LOSs in acute care beds and the ICU could increase the financial burden, decrease health-related quality of life and increase the risks of developing complications such as hospital-acquired infections and ICU-acquired weakness. [16,17] We assume that the committed and organized support gained by following the MCI protocol could minimize the impacts on the EDs and hospitals.…”
Section: Discussionmentioning
confidence: 99%